2018
DOI: 10.3892/ijo.2018.4650
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin enhances the suppressive effects of cisplatin on lung cancer growth through PTX3 glycosylation via AKT/NF-κB signaling pathway

Abstract: Long pentraxin-3 (PTX3) is an inflammatory molecule related to cancer proliferation, invasion, and metastasis. Many studies have highlighted the significance of glycosylated molecules in immune modulation, inflammation and cancer progression. Moreover, aberrant glycosylation of cancer cells is linked to chemoresistance. This study aimed to develop effective therapeutic strategies for deglycosylation of PTX3 (dePTX3) in order to enhance chemosensitivity to cisplatin (Cis) in lung cancer treatment. The A549 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Qi et al reported that silencing of PTX3 mitigates the LPS-induced in ammatory response in BV-2 cells and mice, which occurs by down-regulating the TLR4/NF-κB signaling pathway [65]. Ahmmed et al showed when they caused the deglycosylation of PTX3 and changed its function, the AKT/NF-κB signaling pathway was inactivated [66]. These data indicated that PTX3 pathway could play a signi cant role in K284-6111 inhibiting effect on CHI3L1-mediating M1-speci c neuroin ammation associated with AD development.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al reported that silencing of PTX3 mitigates the LPS-induced in ammatory response in BV-2 cells and mice, which occurs by down-regulating the TLR4/NF-κB signaling pathway [65]. Ahmmed et al showed when they caused the deglycosylation of PTX3 and changed its function, the AKT/NF-κB signaling pathway was inactivated [66]. These data indicated that PTX3 pathway could play a signi cant role in K284-6111 inhibiting effect on CHI3L1-mediating M1-speci c neuroin ammation associated with AD development.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer cells, deglycosylation of human pentraxin-3 (PTX3) protein by TM enhanced the sensitivity to therapy via AKT/NF-κB signaling pathway. TM inhibits glycosylation of plasma membrane receptors, resulting in impaired transport of these receptors to the cell surface [76,77].…”
Section: Tunicamycinmentioning
confidence: 99%
“…TM arrested underglycosylated FLT3-ITD in an endoplasmic reticulum-bound form to activated STAT5 [78]. But mere retention of FLT3 in the endoplasmic reticulum is not sufficient to activate signaling and mutation of FLT3 is necessary for initiation of downstream STAT5 signaling from the endoplasmic reticulum [77]. In FLT3-ITD mutant cells, TM has been confirmed to arrest underglycosylated FLT3-ITD in the endoplasmic reticulum and to promote STAT5 activation [55,78].…”
Section: Tunicamycinmentioning
confidence: 99%
“…It activates effectors under inflammatory conditions and is an important component of innate immunity [8]. PTX3 expression is regulated by various signaling pathways, such as NF-κB, JNK and PI3K/Akt signaling pathways [9]. PTX3 was originally identified as the inducible genes of IL-1 and TNF-α, which are widely involved in the regulation of inflammatory diseases, such as pneumonia, cystitis and cancer-related inflammation [10].…”
Section: Introductionmentioning
confidence: 99%